PENGEMBANGAN SISTEM PENCATATAN DAN PELAPORAN INSIDEN KESELAMATAN PASIEN (IKP) BERBASIS WEB DI RUMAH SAKIT - Siti Zahro (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: In an effffort to improve patient safety in Hj. Anna Lasmanah Hospital Banjarnegara Regency, this study developed a web-based incident reporting system. This is an effffective tool with advantages suitable for promoting an open culture for patient safety. Objectives: Improve incident reporting mechanisms in hospital considering the comfort, convenience and confifidentiality, so that it can support the efffforts of improve patient safety. Methods:This was action research design, conducted at the Hj. Anna Lasmanah Hospital Banjarnegara Regency. Research participants amounted to 7 (seven) people. The research began with the identifification of needs through interviews, observation and study of documentation. The process of making the prototype systems was based on the results of the identifification of needs. The evaluation process was carried out using a questionnaire, distributed to 40 participants to assess usability. While for evaluating importance, scientififically acceptable, transparency, and feasibility, we conducted observation and interviews with participants. Interview data were analyzed qualitatively, through the process of data transcription, coding and categorization. Data from questionnaires done by calculating the average. Results: This research resulted a prototype incident reporting system that accommodated to the basic needs of the user. Most participants (91,96%) were satisfified with the application developed. The prototype system is considered appropriate to be applied in the hospital, with some suggestions for the need for improvement regarding the application program, network infrastructure and human resource capacity. Conclusion: A prototype system developed was considered can improve incident reporting mechanisms in hospital considering the comfort, convenience and confifidentiality, so that it can support the efffforts of improve patient safety.